Recent Developments in Building Diagnosis Techniques - Delgado, João M.P.Q.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a collection of recent research on building diagnosis techniques related to construction pathology, hygrothermal behavior and durability, and diagnostic techniques. It highlights recent advances and new developments in the field of building physics, building anomalies in materials and components, new techniques for improved energy efficiency analysis, and diagnosis techniques such as infrared thermography. This book will be of interest to a wide readership of professionals, scientists, students, practitioners, and lecturers.
Use of three dimensional laser scanner to substrate/mortar contact area quantification and main parameters affecting this property identification -- ETICS' pathologies -- Criteria for application and identification of anomalies on the façades of buildings with the use of passive infrared thermography -- The wind driving rain and the building pathologies: directional driving rain, experimental simulation and quantification of wetness areas -- Good practice: analysis of the vulnerability of the seven churches of Monza -- On the use of infrared thermographic measurements for evaluating the airtightness of the building envelope -- Risk assessment of urban fire - Proposal of a method for analysis and management of existing building -- Evaluation of moisture transfer in external plaster finishing to improve their conservation -- The use of fibre reinforced polymers in the rehabilitation of damaged masonry walletes -- Energy efficient rehabilitation measures for the Portuguese residential buildings constructed in the 1960-1990 period -- Ventilation system for drying out buildings after a flood -- Permeability assessment from porous size distribution function.
Keywords: Buildings -- Repair and reconstruction; Buildings -- Maintenance; Building materials; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Buildings -- Environmental engineering; Energy policy; Energy and state; Building Repair and Maintenance; Structural Materials; Engineering Thermodynamics, Heat and Mass Transfer; Building Physics, HVAC; Energy Policy, Economics and Management